Measurement properties of instruments used to measure health-related quality of life in pediatric and adults patients with inherited epidermolysis bullosa: A systematic review and meta-analysis protocol - Mario Gómez-Martínez; Greta Arias-Merino; Juan Benito-Lozano; Ana Villaverde-Hueso; Renata Linertová; Verónica Alonso-Ferreira (PLoS ONE, 2025)
Inherited Epidermolysis Bullosa (EB) is a group of rare, genetic skin diseases characterized by extreme fragility of the skin and mucous membranes, leading to blistering and wounds in response to minimal trauma or friction. These clinical manifestations significantly reduce health-related quality of life (HRQoL). The objective of this protocol article is to provide information about the methods planned to be used to assess the measurement properties of HRQoL instruments specifically developed for EB patients of all age groups through a systematic review and meta-analysis. The protocol followed the Preferred Reporting Items for Systematic Reviews and Meta-analyses Protocols (PRISMA-P) guideline. The literature search will be conducted in PubMed, Web of Science (WOS) and EMBASE, including terminology that aligns with the four key elements of the COSMIN (COnsensus-based Standards for the selection of health Measurement INstruments) research question (construct, target population, measurement properties and type of PROM), as well as the terminology proposed by COSMIN for measurement properties. Studies that include information on measurement properties (specifically, validity and/or reliability) with a sample of patients with inherited EB will be selected. Both title and abstract screening and full text review, will be conducted by two independent reviewers using the Rayyan tool. In addition, the risk of bias will be assessed using the COSMIN-Risk of Bias checklist. The data from each study and each measurement property will be summarized in accordance with the COSMIN guidelines. The evidence gathered will strive to adjudicate data on measurements properties of HRQoL instruments used in EB patients, and the limitations of the future systematic review will be discussed. Ultimately, results of the future systematic review will help develop more personalized guidelines for the assessment of HRQoL in EB patients of all age groups. The protocol is registered in OSF with registration number vrm87: https://osf.io/vrm87/